Hubungan Dukungan Keluarga Dengan Kepatuhan Minum Obat Pasien Skizofrenia di Poliklinik Psikiatri Rumah Sakit X - Zuhriya Meilita; Devi Fitriyani (Jurnal Afiat : Kesehatan dan Anak, 2021)
Mental disorders are one of the four main health problems in developed and developing countries. Cases of mental disorders in Indonesia have increased, it can be seen from the increase in the prevalence of households with ODGJ in Indonesia. An increase per 1000 households there are 7 households that have family members with ODGJ. The purpose of the study was to determine the relationship between family support and medication adherence in schizophrenic patients at the in Psychiatry Polyclinic X. The research method used is descriptive correlation with cross sectional approach. The total population is 257 people. The sample was taken using the Slovin formula with the respondent search technique using purposive sampling. Collecting data using a questionnaire. The analysis used univariate and bivariate using chi-square with α = 5 %. The results of the study on family support for schizophrenic patients at the Psychiatric Polyclinic X from 72 respondents, it was found that most of the respondents had poor family support, namely 37 respondents (51.4%). Based on the results of the analysis using chi-square, it was found that the value of ρ Value = 0,000 < 0,05 so that H0 was rejected and H1 was accepted. The conclusion is that there is a relationship between family support and medication adherence in schizophrenia patients at the Psychiatry Polyclinic X.